Papago Park: master plan redevelopment - Sobczynski, Katie Ann (Kansas State University, 2009)
Papago Park is an extraordinary urban space that has a rich history in the development of the Phoenix metropolitan area. The park was settled by pre-historic civilizations and has since been a significant recreation space for more recent generations. Although the park has been treasured among locals for ages, the development of large tourist attractions and other program elements have not been part of a cohesive park design. The park lacks a sense of unity and a strong local identity. Papago is unique in the fact that it is the only major urban park that showcases the native Sonoran Desert ecosystem. Conservation of these limited areas of native landscape is important. There is great potential for Papago to better respond to the environmental, educational, and recreational needs of the public. With this master plan, development of Papago Park is guided in order to unify park elements and strengthen its identity. It is intended that a cohesive park design which focuses on conservation of native landscape with an integrated social program will help Papago Park gain proper recognition on a regional and national scale.
Keywords: Papago Park; Phoenix, Arizona; park planning; park design; master plan; unify; Landscape Architecture (0390); Recreation (0814); Urban and Regional Planning (0999)